PENERAPAN TEKNIK TIRU MODEL DALAM PEMBELAJARAN MENULIS BAHASA INDONESIA - Nur Holifatuz Zahro (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2017)
In their experiences wrote, modeling is strategy that departs from the act of reading text model, analyze the text model, and practice writing by imitating construction model text. Through the phases as students obtain samples of, the introduction of and understanding writings, elements understand the or technique of writing with right. This is through a strategy of students can build their knowledge of the a manner of writing that right. Not only that, the existence of the text model also assist in reducing difficulty mengerangkakan students at the time of its initiative on it and he poured into the shape of the text